Становлення та трансформація земельних правовідносин у системі політико-правових учень (на прикладі XVIII - першої половини ХХ століття) - Жиравецький, Т. М.; Zhyravetskyi, T. M. (Правові новели. – 2020. – № 12, т. 3. – С. 7-12, 2020)
Проаналізовано становлення та трансформації земельних правовідносин у системі політико-правових учень (на прикладі XVIII –першої половини ХХ століття). Констатовано, що в цей час здійснилося: розмежування особистого царського і державного майна, що перебували єдиним комплексом, тобто виникли підстави для розрізнення приватного та публічного власності, розведення характеру прав та повноважень; ліквідація особливих юридичних статусів колишніх самостійних володінь і правових преференцій; виникнення помісного землеволодіння як масової форми умовного тримання і поводження його в основний засіб утримання і забезпечення «государевих людей»; скорочення церковного землеволодіння і звуження правомочностей даної категорії власників; звуження селянського землеволодіння і поступове переведення селян-власників на стан державних селян - визнання селянських земель, раніше вільних від феодальної ієрархії земельних прав, державними. Спочатку, в основі земельних відносин лежала повна свобода особистості, яка доходила до права розпоряджатися собою і своїм майном на умовах, що визначаються лише своїм розсудом і положенням в суспільстві. Саме тому існувало безліч різних форм залежного володіння землею, але поступово ця свобода призводить до встановлення як особистої, так і поземельної залежності між політично і економічно сильними і слабкими представниками землеволодіння і обороту землі.

The scientific article is devoted to the research and complex analysis of the formation and transformation of land relations in the system of political and legal doctrines (on the example of XVIII - the first half of the twentieth century). Taking into account the doctrinal research, it is stated that the presented period is probably the most significant in the history of land ownership formation. At this time there was: the separation of personal royal and state property, which were a single complex, ie there were grounds for distinguishing between private and public property, the separation of the nature of rights and powers; elimination of special legal statuses of former independent possessions and legal preferences; the emergence of local land tenure as a mass form of conditional detention and its treatment as the main means of maintaining and providing "sovereign people"; reduction of church land ownership and narrowing of the powers of this category of owners; narrowing of peasant land tenure and the gradual transfer of peasant owners to the state of state peasants - recognition of peasant lands, previously free from the feudal hierarchy of land rights, state. Initially, the basis of land relations was the complete freedom of the individual, who came to the right to dispose of themselves and their property on terms determined only by their discretion and position in society. That is why there were many different forms of dependent land ownership, but gradually this freedom leads to the establishment of both personal and land dependence between politically and economically strong and weak representatives of land tenure and land turnover. When considering the various forms and types of land use and land tenure, the author concludes that the content of a particular right depended on the status of the subject of this right. In addition, in the study period there is a fairly extensive system of land rights, associated primarily with the peculiarities of the class system, as well as a large and multinational territory.

Проанализировано становление и трансформация земельных правоотношений в системе политико-правовых учений (на примере XVIII – первой половины ХХ века). Констатировано, что в это время происходило: разграничение личного царского и государственного имущества, находившихся единым комплексом, то есть возникли основания для различения частной и публичной собственности, разведения характера прав и полномочий; ликвидация особых юридических статусов прежних самостоятельных владений и правовых преференций; возникновение поместного землевладения как массовой формы условного содержания и обращения его в основное средство содержания и обеспечения «государевых людей»; сокращение церковного землевладения и сужение правомочий данной категории собственников; сужение крестьянского землевладения и постепенное перевод крестьян-владельцев в состояние государственных крестьян – признание крестьянских земель, ранее свободных от феодальной иерархии земельным правам, государственными.
Formation and transformation of land relations in the system of political and legal doctrines (on the example of XVIII – the first half of the twentieth century)
Keywords: історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; земельні відносини; land relations; земельные отношения; інститут приватної власності на землю; institution of private ownership of land; институт частной собственности на землю; українські території у складі Російської імперії; Ukrainian territories within the Russian Empire; украинские территории в составе Российской империи; правове регулювання; legal regulation; правовое регулирование; форми власності; type of ownership; формы собственности; українські губернії; Ukrainian provinces; украинские губернии